The Variants of Technologies of Suture Fixation in Case of IOL-Capsular Bag Complex III–IV Degree Dislocation - D. I. Ivanov; V. N. Nikitin (Oftalʹmologiâ, 2020)
Purpose. To present the results of several technologies for suture fixation in case of IOL-capsular bag complex III–IV-degree dislocation and to estimate their impact on IOP. Patients and Methods. We have analyzed 42 cases of IOL-capsular bag complex dislocation complicated by absence of capsular support which were divided into three groups. Group 1 included 4 cases of complex fixation to the sclera (presence of capsular ring, IOLs with closed loop haptics such as T-26, T-28, single-piece IOLs with massive haptics such as Asphina). Suture fixation was performed in the ciliary sulcus projection with capture of haptics or capsular ring and buried knots in capsular pockets. Group 2 included 27 cases with iris suture fixation with capture of haptics or fibrotic capsular bag on a 30G needle. Reposition and support of dislocated IOL-capsular bag complex was performed with a bent 30G needle inserted through pars plana. Group 3 included 11 cases with iris suture fixation with additional surgical manipulations (anterior vitrectomy, removal of fibrotic anterior and posterior capsules, complete removal of the capsular bag with cortex, surgical dissection of opacified posterior capsule). The specific feature was the use of vitreotome needle for IOL-capsular bag complex centration and fixation as well as for subsequent removal of capsular bag fibrosis, secondary cataract or cortex. Results. Intraoperative complications included 3 cases of slight bleeding during iris perforation. Postoperative  complications included 4 cases of inflammatory reaction in the form of fibrin in the pupil. No cases of hemophthalmia associated with the insertion of 30 G needle or port in the eye cavity were marked. Two patients developed pseudoexfoliation glaucoma treated with hypotensive drops. In the early and late postoperative period in all patients of all the groups stable position of IOL-capsular bag complex was marked. Conclusion. Use of discussed techniques gives a possibility to obtain high visual prognosis, low probability of IOP elevation and stable position of IOL-capsular bag complex in all the three groups.